Towards new weather and climate baselines for assessing weather and climate extremes, impacts, and risks - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2017)
Initiatives to recover (sourcing, imaging, digitizing) historic datasets for generating more accurate longterm climate models have only gained momentum over the last decade, despite a long precedent of compelling arguments as to the value of historic weather observations (Le Roy Ladurie, 1972; Lamb, 1977). Although such work is relatively well established in Europe, the United States, China, and Japan; Southeast Asia currently has a dearth of data rescue initiatives with a long historical focus. The reasons behind this include a perception of the paucity of surviving data; the scattered nature of data due to shifts between colonial rule and independence and, later regime changes; a lack of local resources to develop data recovery projects. By way of example, the Southeast Asian Climate Assessment & Dataset (SACA&D) Digitisasi Data Historis (DiDaH) project, now completed, was limited by the fact that the bulk of observations recovered and digitized were in the post 1940s-50s period (apart from Indonesia in the South East Asian region) and, their data rescue was directed at National Meteorological Service (NMS) records only, with generally a heavy focus on temperature and precipitation data. ACRE SEA has a wider scope, with a longer historical timeframe (especially with a pre 1940s-50s observations focus) and broader record collection base, using archives, libraries, and online sources across the region and internationally. In fact, the SACA&D DiDaH project.